Blood glucose level impact on biometric parameters, refraction and intraocular pressure in patients with subcompensated insulin-requiring type II diabetes - L. A. Mineeva; L. I. Balashevich; A. A. Kozhukhov; A. A. Baranov; L. B. Shubin; A. V. Kabanov (Российский офтальмологический журнал)
Purpose. To study the relationship of biometric parameters, visual acuity, eye refraction and intraocular pressure (IOP) with blood glucose levels and glycated hemoglobin (HbA1c) in patients with subcompensated insulin-requiring type II diabetes mellitus. Material and methods. Ophthalmic monitoring lasted 3 years, the experience of insulin therapy — 6 years. 32 patients (27 women and 5 men) with insulin-requiring diabetes mellitus and no severe general diabetic complications or concomitant eye pathology were monitored for 3 years. The patients’ average age was 60.4 ± 5.3 years; average weight 94.3 ± 16.5 kg; average height 163.4 cm; average BMI (body mass index) was 29.93 kg/m2, all received insulin treatment for 6 years. Patients determined the level of blood glucose themselves on a daily basis using individual “Accu-Check” and/or “OneTouch select” glucometers, supplemented by endocrinologist checks on scheduled examinations once a month. The level of glycated hemoglobin (HbA1c) was determined once every 3–6 months. The 3-year ophthalmic monitoring involved both eyes and included biomicroscopy, autorefractometry, pneumotonometry, measurement of the anterior-posterior axis, the depth of the anterior chamber and lens thickness; pachymetry of the cornea in the central optical zone, and ophthalmoscopy. Visometry was performed according to ETDRS (Early Treatment Diabetic Retinopathy Study Research Group) requirements. Results. The impact of blood glucose level on visual acuity (Spearman R = 0.18/-0.23, t (N-2) = 1.07/-1.34, p = 0.1) is higher than that of HbA1c (Spearman R = 0.07/-0.15, t (N-2) = 0.4/-0.8, p = 0.65) The higher the glucose level, the lower the depth of the anterior chamber and the shorter the APA. In contrast, the higher the level of HbA1c, the thicker the cornea in the central optical zone. Both the glucose and the HbA1c levels reveal a similar positive correlations with IOP. A refraction shift toward myopia from 42 % to 55 % was shown to correlate to HbA1c, and a  corresponding reduction of hyperopia share was revealed. Conclusions. In patients with  subcompensated insulin-requiring diabetes mellitus type II, biometric parameters, refraction and intraocular pressure are determined by changes in the level of blood glycemia.